Characterising mental health and addictions and assault-related health care use in the year prior to death: a population-based linked cohort study of homicide victims. (2021) - O'Neill, Meghan; Buajitti, Emmalin; Donnelly, Peter D; Kornas, Kathy; ,; Rosella, Laura
No abstract available